A PROFICIENT APPROACH TO SELF-DIRECTED LEARNING (Scientific journal of the Fergana State University, 2024)
Self-directed learning (SDL) empowers learners to take control of their educational experiences, fostering lifelong learning and adaptability. This study investigates the efficacy of SDL methods, comparing traditional instructor-led approaches with self-directed techniques in higher education settings. Through a mixed-methods approach, combining quantitative surveys and qualitative interviews, we assess the outcomes in terms of academic performance, learner satisfaction, and skill acquisition. Results indicate that SDL significantly enhances intrinsic motivation and critical thinking skills, although it requires a robust framework to ensure success. We discuss the implications of these findings for curriculum design and educational policy.